2009
DOI: 10.2147/ndt.s4874
|View full text |Cite
|
Sign up to set email alerts
|

SAFA: A new measure to evaluate psychiatric symptoms detected in a sample of children and adolescents affected by eating disorders. Correlations with risk factors

Abstract: In order to evaluate the psychiatric symptoms associated with a diagnosis of eating disorders (ED) we have administered a new psychometric instrument: the Self Administrated Psychiatric Scales for Children and Adolescents (SAFA) test. SAFA was administered to a cohort of 97 patients, aged from 8.8 to 18, with an ED diagnosis. Age, body mass index (BMI) and BMI standard deviation score were analyzed. Furthermore, while looking for linkable risk factors, we evaluated other data that took an influence over the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The SAFA battery was validated. It showed good psychometric properties (Cianchetti and Sannio Fascello, 2001;Franzoni et al, 2009;Pellicciari et al, 2012). In our study, the Cronbach's test showed α values of 0.84 for answers to SAFA anxiety questions and of 0.77 for SAFA depression.…”
Section: Anxiety and Depressive Symptomssupporting
confidence: 54%
“…The SAFA battery was validated. It showed good psychometric properties (Cianchetti and Sannio Fascello, 2001;Franzoni et al, 2009;Pellicciari et al, 2012). In our study, the Cronbach's test showed α values of 0.84 for answers to SAFA anxiety questions and of 0.77 for SAFA depression.…”
Section: Anxiety and Depressive Symptomssupporting
confidence: 54%
“…Anxiety was measured using the Self-Administered Psychiatric Scales for Children and Adolescents (SAFA) battery [ 21 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…SAFA is a self-reporting questionnaire for investigating the specific components of anxious, depressive and somatic symptoms. Many Italian studies have used these scales to assess different symptomatology associated with disorders like Tourette Syndrome, eating disorders or learning disabilities (Franzoni et al, 2009;Termine et al, 2011;Nacinovich et al, 2012;Pellicciari et al, 2012;Mammarella et al, 2014). The SAFA scales measure: Anxiety (SAFA-A), Depression (SAFA-D), Obsessive-Compulsive symptoms (SAFA-O), Psychogenic eating disorders (SAFA-P), Somatic Symptoms and Hypochondria (SAFA-S) and Phobias (SAFA-F).…”
Section: Instrumentsmentioning
confidence: 99%